Recontextualizing Abdurrahman Wahid’s Rejection of Islamic-State Formalization: An Interfaith Socio-Legal Critical Discourse Analysis - Kholisin; Abdul Basid; Hassan Youssef; Nur Faizin (International Journal of Law and Society, 2026)
Indonesia's post-Reformasi debates over religion and the state have renewed contestations over Pancasila, constitutional pluralism, and Sharia-oriented governance. This study examines how Abdurrahman Wahid's rejection of Islamic-state formalisation is linguistically constructed, circulated, and recontextualised across interfaith reception. Using socio-legal qualitative Critical Discourse Analysis (CDA), it analyses a translated transcript of Wahid's lecture and open-ended narratives from 16 interfaith respondents. The analysis follows Fairclough's textual, discursive-practice, and social-practice levels, focusing on lexis, modality, evaluation, actor representation, and power relations. The findings show that Wahid distinguishes the obligation to defend the country from the non-obligation to establish an Islamic state, authorising this position through NU deliberation, ulama authority, the Jihad Resolution, and plural national belonging. Reception narratives reveal a discursive split: respondents often reject Islamic-state formalisation while selectively endorsing punitive Sharia as justice. The study contributes to socio-legal CDA by integrating transcript evidence, contemporary interfaith reception, and power analysis. It recommends stronger legal safeguards and interfaith civic education to sustain inclusive citizenship.